Estimates of output, income value added and employment multipliers for the Maltese economy - Ian P. Cassar (Central Bank of Malta, 2015)
The study presents the first published estimates of industry specific multipliers which are derived utilizing a highly disaggregated symmetric input-output table for the Maltese Economy for 2008 which adheres to Eurostat System of National and Regional Accounts (1995). The application of selected input-output models, which are a deterministic class of models, to the symmetric input-output table allows for the estimation of industry specific multipliers. The aim of this study is to derive output, income, value added and employment multipliers at highly disaggregated industry level to study how an exogenous shock to the final demand of each of these industries would affect the Maltese economy.
Keywords: C67; D57; 330